The Relevance Of Cognitive Behavioral Therapy For Managing The Quarter-Life Crisis In Early Adulthood From An Qur’anic Perspective - Rahmawati Rahmawati; Rifqatul Husna (JURNAL AT-TURAS, 2026)
The Quarter-Life Crisis (QLC) is a crisis phase in early adulthood characterized by anxiety, uncertainty about the future, low self-confidence, and feelings of being left behind due to social comparison, particularly through social media. This condition is closely related to cognitive distortions that influence how individuals perceive themselves. This study aims to examine verses from the Qur’an that are relevant to Cognitive Restructuring techniques within the Cognitive Behavioral Therapy (CBT) approach as a means of managing negative thought patterns in individuals experiencing a Quarter-Life Crisis. The study employs a library research method using a qualitative-descriptive approach and thematic interpretation analysis. The primary data source is the Qur’an, with the main references being Tafsir Al-Misbah by M. Quraish Shihab and Tafsir Al-Azhar by Buya Hamka, while secondary data sources come from psychology journals and research related to CBT as well as the phenomenon of social comparison. The analysis was conducted through theme identification, the collection of relevant verses, an examination of the verses’ meanings based on the commentaries, and the mapping of Qur’anic concepts to the principles of Cognitive Restructuring. The results of the study indicate that QS. An-Nisa’/4:32, QS. Ibrahim/14:7, and QS. At-Taubah/9:51 align with the principles of Cognitive Restructuring. QS. An-Nisa’/4:32 guides individuals to avoid social comparison and focus on their own efforts; QS. Ibrahim/14:7 instills a mindset of gratitude as a form of positive emotion regulation; while QS. At-Taubah/9:51 emphasizes the importance of tawakal as a form of acceptance of Allah’s decree after making one’s best effort. This study contributes by offering a conceptual framework for the integration of Qur’anic values and Cognitive Restructuring techniques in CBT to understand and address the phenomenon of QLC. These findings are expected to serve as a reference for the development of Qur’an-based counseling approaches and to open opportunities for empirical research to test the effectiveness of this integration among individuals experiencing QLC.